Physical Activity and Academic Procrastination in college students: Self-Efficacy as a Mediator - Isna Asyri Syahrina; Sari Rahmadani (Universitas Ahmad Dahlan, 2026)
Academic procrastination remains a persistent challenge in higher education, negatively affecting students’ academic performance and psychological well-being. Although previous studies have identified various determinants of procrastination, limited attention has been given to the psychological mechanism through which physical activity may reduce procrastination behavior, particularly the mediating role of self-efficacy. This quantitative study investigated the relationship between physical activity, self-efficacy, and academic procrastination among university students. The participants were 156 students from the Information Systems Department at Universitas Putra Indonesia YPTK Padang during the even semester of the 2024–2025 academic year, selected using simple random sampling. Data were collected using the Academic Procrastination Scale, Self-Efficacy Scale, and Physical Activity Scale, and analyzed using SmartPLS 3. The findings revealed that physical activity negatively predicted academic procrastination (β = −0.474, p < .001) and positively predicted self-efficacy (β = 0.489, p < .001). In addition, self-efficacy negatively predicted academic procrastination (β = −0.164, p = .013) and partially mediated the relationship between physical activity and academic procrastination. These findings suggest that engagement in physical activity may help reduce academic procrastination both directly and indirectly through enhanced self-efficacy. The study highlights the importance of integrating physical activity promotion and self-efficacy development into student support programs aimed at minimizing procrastination behavior in higher education settings.